Correlates of the levels of various immunoreactive hormones and the quality of buffalo (Bubalus bubalis) semen during different seasons - SIDHU, K S; GILL, H K (The Indian Journal of Animal Sciences, 2013)
Immunoreactive progesterone, prolactin and luteinizing hormone (LH) are present in the seminal plasma of buffalo. Variation in the levels of these hormones during different seasons of the year were nonsignificant (p